2015
DOI: 10.1186/s40697-015-0051-z
|View full text |Cite
|
Sign up to set email alerts
|

An Education Initiative Modifies Opinions of Hemodialysis Nurses towards Home Dialysis

Abstract: BackgroundIt has been shown that in-center hemodialysis (HD) nurses prefer in-center HD for patients with certain characteristics; however it is not known if their opinions can be changed.ObjectiveTo determine if an education initiative modified the perceptions of in-center HD nurses towards home dialysis.DesignCross-sectional survey of in-center HD nurses before and after a three hour continuing nursing education (CNE) initiative. Content of the CNE initiative included a didactic review of benefits of home di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Physicians may not have the time in a busy office schedule to educate; nephrology practices may not totally embrace educational programs offered by large dialysis organizations (LDOs), yet not have a structured program themselves; short office sessions may be insufficient to achieve adequate education; and lack of experience or confidence in PD may prevent effective discussion of this option with patients and families. The opinions of ICHD nurses toward home modalities can also have a negative impact on PD growth . As noted in a previous publication and depicted in Fig.…”
Section: Positioning Modality Selection Within An Integrated Kidney Cmentioning
confidence: 66%
“…Physicians may not have the time in a busy office schedule to educate; nephrology practices may not totally embrace educational programs offered by large dialysis organizations (LDOs), yet not have a structured program themselves; short office sessions may be insufficient to achieve adequate education; and lack of experience or confidence in PD may prevent effective discussion of this option with patients and families. The opinions of ICHD nurses toward home modalities can also have a negative impact on PD growth . As noted in a previous publication and depicted in Fig.…”
Section: Positioning Modality Selection Within An Integrated Kidney Cmentioning
confidence: 66%
“…recognition of home dialysis' underuse, 2,26,27 with educational initiatives by many organizations (including the National Kidney Foundation, the International Society for Peritoneal Dialysis, the American Society of Nephrology, universities, and dialysis providers) aimed at alleviating nephrologists' and nephrology trainees' discomfort with prescribing home modalities. [28][29][30] Although the PPS only directly incentivized home dialysis use in United States patients with Medicare Parts A and B, we also found that the PPS was associated with increased home dialysis use in incident patients with other forms of insurance in the United States. Because United States patients with Medicare constitute the majority of patients at most dialysis facilities, we hypothesize that the PPS catalyzed a significant change in provider attitude toward the entire dialysis population.…”
Section: Discussionmentioning
confidence: 62%
“…There may be greater risk of training failure in doing so, but it allows for objective evaluation of the patient’s ability to undertake self-care HD [ 12 ]. A recent study has established that an education initiative can modify the opinions of in-centre HD nurses towards home modalities and this should be incorporated into the many strategies for expanding a home HD programme [ 13 ].…”
Section: Discussionmentioning
confidence: 99%